CHILD AND MATERNAL MALNUTRITION IN THE POST-MDG ERA – QUALITATIVE ANALYSIS OF CHALLENGES AND POSSIBLE WAY-OUT: A SOCIAL NETWORK ANALYSIS OF POPULATION THERAPEUTIC STRATEGIES - Attaullah Jan; Syed Saleem Shah; Shumaila Bakht; Sunara Shafiq; Iftikhar Alam (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Child and maternal malnutrition is a major population health problem of Pakistan. After millennium development goals (MDG), the sustainable development goals (SDG) is an effective strategy to address malnutrition in a more collaborative manner. The recent Covid-19 pandemic has badly affected SDGs efforts. Data on the effects of Covid-19 on implementation of nutrition SDGs - an extension of the MDGs, is scarce. Therefore, the present study investigated the challenges posed by Covid-19 and the priority actions needed to cope with these challenges. The study utilized mixed methodology that included review of published official documents and interviews of the relevant stakeholders. Data was collected in a questionnaire on questions related to the effects of Covid-19 on nutrition SDGs. The social network analysis was performed to derive key themes from the qualitative data obtained from the respondents. Gephi 0.10.1 software package was used for data analysis and visualization. The results show responded perceived ‘funds distribution’, ‘social mobilization’, ‘charity mobilization’, ‘innovation in research’, ‘education/awareness’, ‘capacity building’ and ‘budget curtailing’ as the main challenges posed by Covid-19 to child and maternal nutrition. In response what can be done to address these challenges, responded suggested these: ‘nutrition-sensitive strategies’, devolution of power’, ‘political stability’, strong nutrition surveillance system’, ‘multi-sectoral approach’, ‘controlling food costs’, ‘nutrition governance’, ‘stronger monitoring/evaluation strategies’ etc. In conclusion, Covid-19 has badly and negatively affected nutrition SDGs and there is an urgent call for more integrated and collaborative efforts to successfully conclude the SDGs agenda by 2030.